Letters to a Young Pharmacist : Even More Sage Advice on Life and Career. - Cantrell, Susan A. (American Society of Health-System Pharmacists, 2022)
Letters to a Young Pharmacist is the next installment of the ASHP Letters series created to inspire pharmacists through all stages of their professional journey.